Risk attitudes and the value of risk transformations. (22nd August 2013) - Denuit, Michel M.; Eeckhoudt, Louis
Abstract: An increase in risk aversion, defined by a concavification of the utility function, does not always increase the willingness to pay (WTP) for a mean‐preserving reduction in risk. This is why Ross (1981 ) proposed a stronger measure of increased risk aversion that maintains for mean‐preserving changes in risk the result obtained by Arrow (1965 ) and Pratt (1964 ) for risk elimination. Ross's (1981 ) contribution was later extended to higher orders using Ekern's (1980 ) notion of a higher‐degree increase in risk. In this paper, we show that these measures remain valid under less restrictive assumptions than those implied by Ekern's (1980 ) approach and we refer to the concept of mean‐preserving stochastic dominance. Finally, we also extend the analysis conducted for the WTP to the willingness to accept.